Building and implementing a level gauge wasted time With teachers and teachers in primary schools - Muhammad Abdul Karim Taher (Zanco Journal of Humanity Sciences)
يعد الوقت من الموارد الهامة النادرة والثمينة لاي منظمة لانه يمثل عنصرا من عناصر العملية الانتاجية , ولحاجة المنظمات الدائمة لاستثمار مواردها بشكل فعال لتحقيق الاهداف التي انشات من اجلها , فلا بد ان يستثمر وقت المنظمة بطريقة فعالة كاحد الموارد المتاحة ،وقد ركزت الدراسة الحالية على مؤشرات هدر الوقت وضياعه وسوء استثماره من خلال كثرة المكالمات الهاتفية والانشغال بالزائرين والمشاكل الاسرية والاجتماعية وعزوفهم عن تثبيت مهامهم بسجل يومي يخطط وينظم ادائهم التربوي والتعليمي ، وقد هدفت الدر اسة الحالية الى قياس The time of the important resources of rare and precious for any organization because it represents an element of the production process elements, and need permanent organizations to invest their resources effectively to achieve the goals that have established for it, it must invest time in the organization in an effective manner as one of the resources available, and the current study focused on the waste indicators Time, and poor investment through frequent telephone calls and preoccupation with visitors and family and social problems and their reluctance to install their tasks with a daily record of planning and organizing their educational and educational performance . The current study aimed to measure مستوى هدر الوقت لدى المعلمين والمعلمات في المدارس الأبتدائية ، وقد قام الباحث ببناء مقياس هدر الوقت The level of waste of time among teachers and teachers in primary schools , and the researcher built a measure of wasting time والذي تكون بصيغته النهائية من ( 39 ) فقرة،بعد ان تم أس تخراج صدق وتمييز الفقرات ، وتم اس ت خراج صدق وثبات ال مقياس بأستخدام الوسائل الاحصائية المناسبة،وبعد أن طبق المقياس على عينة التحليل الاحصائي البالغة (400) معلما ومعلمة ، وكذلك طبق الباحث المقياس على عينة التطبيق النهائي البالغة (200) معلما ومعلمة Which will be in its final form (39) paragraph, having been as extraction sincerity and distinction paragraphs were as yet abscess validity and reliability of the scale using appropriate statistical methods, and after the measure was applied to a sample of statistical analysis amounting to (400) teachers, as well as dish researcher The sample on the final application sample of (200) is marked and marked والتي اختيرت بالاسلوب العشوائي الطبقي ،وقد توصلت الدراسة الى ان مقياس هدر الوقت ، يتمتع بخصائص سيكومترية جيدة ،ووجود مستوى عالي من Which was chosen by the method of random class , and the study found that the measure of time wasting , has good Sicometric characteristics, and a high level of هدر الوقت Wasting time لدى عينة البحث I have a research sample , ووجود أثر للجنس في , And the presence of a gender impact قياس Measurement مستوى هدر الوقت ولصالح عينة المعلمات , ووجود اثرا لسنوات الخبرة العلمية في هدرالوقت The level of waste of time and for the benefit of sample parameters , and the presence of years of scientific experience in the waste of time ولصالح الفئة الاولى ، For the first category , وقد أوصت الدراسة ا مكانية استخدام ال مقياس من قبل وزارة التربية ومدراء المدارس الأبتدائية The study recommended the use of the scale by the Ministry of Education and principals of primary schools , واقترحت الدراسة , The study suggested اجراء دراسة مماثلة على مدراء المدارس ومقارنة نتائجه ا مع نتائج الدراسة الحالية A similar study on school principals and comparing its results with the results of the current study ،وبناء برنامج أرشادي تربوي من أجل تبصير المعلمين والمعلمات باهمية الوقت وعدم هدره اثناء الدوام في المدارس الأبتدائية . , And the construction of educational educational program in order to enlighten teachers and teachers on the importance of time and not wasting it during work in elementary schools .